Determination of glycemic index and glycemic load of hospital diets served for diabetics - Lemos, Karenn Haubricht (2017)
AIMS: To determine the glycemic index and the glycemic load of diets usually offered by hospitals to patients with diabetes mellitus.METHODS: A cross-sectional study evaluated menus served to diabetic inpatients of hospitals in the city of Curitiba, Parana, Brazil. Analyzing the menus, we determined the energy content, macronutrients, glycemic index and glycemic load of the meals offered to the patients. RESULTS: Five general hospitals of the city participated in the study and 10 menus for diabetes were evaluated. The structure of the menus was different mainly in the quantitative supply of fruits and milk. Diets ranged from 1317.6 to 2013.2 kcal, with 18.9 to 27.6% of proteins, 21.9 to 29.4% of lipids, 48.2 to 53.3% of carbohydrates and 24.7 to 33.6 g of fibers. Daily glycemic index ranged from 47 to 57% and daily glycemic load from 81 to 109%.CONCLUSIONS: All offered diets were hyperproteic, normolipid and normoglicidic. However, inadequate levels of glycemic load were observed in all the evaluated menus, although with adequate levels of glycemic index. It is necessary to review the diet plans elaborated for diabetics, aiming at the best dietary treatment for this population.